A Policy Analysis of Rural Development Schemes in Algeria: From Agrarian Reform to Knowledge Based Development - abdelkader, nouibat (جامعة المسيلة, 2008)
This paper tries to look and the different developmental schemes implemented by the Algerian government and their impact on the developmental processes of the agricultural sector. The methodology used is policy analysis. Policy analysis can be defined as "determining which of various alternative policies will most achieve a given set of goals in light of the relations between the policies and the goals" However, policy analysis can be divided into two major fields. Analysis of policy is analytical and descriptive